The Indonesian Presidency: The Shift from Personal toward Constitutional Rule - McIntyre, Angus (Rowman & Littlefield Publishers, 2005)
This pioneering study of the Indonesian presidency significantly redefines our understanding of Indonesian politics from independence to the present. Angus McIntyre blends political biography with constitutional history to locate Indonesian leaders within both Indonesian cultural frameworks and the global biographical literature on political leaders.The Indonesian Presidency shows how Indonesia's 1945 constitution provided first for the personal rule of presidents Sukarno and Soeharto and then facilitated the shift towards constitutional rule that marked the presidencies of B.J. Habibie, Abdurrahman Wahid, and Megawati Sukarnoputri. This important study elevates the personalities of Sukarno and Soeharto into key explanatory factors for the character of their "Guided Democracy" and "New Order" regimes, respectively. It argues that in 1959 Sukarno began fashioning his system of personal rule, to the detriment of Indonesia's parliamentary democracy. Another constitutional turning point occurred in 1998, when a rudimentary constitutional rule reappeared. The broad shift since 1998 from personal to constitutional rule has its personal counterpoint in the relationship between Megawati and her father, which makes this unique blend of history and biography a powerful tool for understanding the Indonesian presidency. An afterword by the author on the book's website, www.rowmanlittlefield.com/isbn/0742538273, brings readers up to date on Indonesian political developments that have affected the presidency since the book's publication.For an up-to-date afterword by the author, click here; for glossary, click here.